Corporate governance - COWAN, Neil (PRENTICE HALL, 2004)
The way companies are directed and controlled – that’s corporate governance. But really, corporate governance is about the way people behave – corporately and individually and it is about the relationships between companies; their directors and employees and the wider stakeholder community. Corporate Governance – That Works! brings together the best of world-wide corporate governance practice in a non-academic, easy to read way which provides an up-to-date text for everyone to enjoy. Codes, regulations and legislation in the field are referred to but in the context of making corporate governance a practical reality rather than a theoretical study, which relies on large quantities of quoted principles. Directors, managers, auditors and everyone interested in making corporate bodies more responsive to the stakeholder interest will find this book a must-have for their business libraries.